Time Synchronization and Performance of BeiDou Satellite Clocks in Orbit. (5th September 2013) - Chunhao, Han; Zhiwu, Cai; Yuting, Lin; Li, Liu; Shenghong, Xiao; Lingfeng, Zhu; Xianglei, Wang
Abstract : The time model of Beidou satellite clocks is analyzed. The general relations of satellite clocks with the system time are studied. The error sources of two-way radio time transfer between satellites and uplink stations are analyzed. The uncertainty of type A is about 0.3 ns in Beidou system. All the satellite clocks in orbit of Beidou satellite navigation system are evaluated by the clock offsets observed by the two-way radio time transfer. The frequency stabilities at a sample time of 10000 s and 1 day for all the satellite clocks are better than1.0 × 10 - 13 . It means that the performance of Beidou satellite clocks in orbit is consistent with the ground test, and the results in orbit are a little better than those in ground vacuum.